Soil moisture regime and palm height influence embolism resistance in oil palm. (7th August 2019) - Waite, Pierre-André; Schuldt, Bernhard; Mathias Link, Roman; Breidenbach, Natalie; Triadiati, Triadiati; Hennings, Nina; Saad, Asmadi; Leuschner, Christoph
Abstract: With the prospect of climate change and more frequent El Niño-related dry spells, the drought tolerance of oil palm ( Elaeis guineensis Jacq.), one of the most important tropical crop species, is of major concern. We studied the influence of soil water availability and palm height on the plasticity of xylem anatomy of oil palm fronds and their embolism resistance at well-drained and seasonally flooded riparian sites in lowland Sumatra, Indonesia. We found overall mean P 12 and P 50 values, i.e., the xylem pressures at 12% or 50% loss of hydraulic conductance, of −1.05 and − 1.86 MPa, respectively, indicating a rather vulnerable frond xylem of oil palm. This matches diurnal courses of stomatal conductance, which in combination with the observed low xylem safety evidence a sensitive water loss regulation. While the xylem anatomical traits vessel diameter ( D h ), vessel density and potential hydraulic conductivity ( K p ) were not different between the sites, palms in the moister riparian plots had on average by 0.4 MPa higher P 50 values than plants in the well-drained plots. This could largely be attributed to differences in palm height between systems. As a consequence, palms of equal height had 1.3 MPa less negative P 50 values in the moister riparian plots than in the well-drained plots. While palm height was positively related to P 50, D h and K p decreased with height. The high plasticity in embolism resistance may be an element of the drought response strategy of oil palm, which, as a monocot, has a relatively deterministic hydraulic architecture. We conclude that oil palm fronds develop a vulnerable water transport system, which may expose the palms to increasing drought stress in a warmer and drier climate. However, the risk of hydraulic failure may be reduced by considerable plasticity in the hydraulic system and the environmental control of embolism resistance, and a presumably large stem capacitance.